ANALISA PERHITUNGAN DINDING PENAHAN TANAH PADA STA 5+550 JALAN POROS LOA TEBU – SEBULU MODERN KEC.TENGGARONG - UDIN, AHIR (KURVA S JURNAL MAHASISWA, 2014)
The groud as construction materials as well as land foundation of a construction or structure in a dam, risver dike , retaining wall, construction work the way, building and certain requirements both in terms of power and economical. This study aims to analyze calculation dimensions retaining walls land stable to tabilitas shifts, overthrow, capacity and reduction by using type cantilever in road locations the shaft Loa tebu – sebulu modern. Calculation pressure land in count using Rankie calculation theory and stability to the collapse of capacity support land in up in the equation Hansen based on data characteristic teknik ( c and q ). Hasil calculation anchoring the stability of the wall with dimensions cantilever type : wide over (a) 0,30 meters, the foundation (b) 3,50 meters, high the wall (h) 5,00 meters, thick plate (d) 0,50 meters, that secure against stability ouster (Fgl), panning stability (Fgs)ans stability of capacity .